Digital Financial Inclusion and its Determinants: Evidence from Türkiye - Tuğba Güz; Gülden Poyraz (Ekonomi, Politika & Finans Araştırmaları Dergisi)
Facilitating participation in the financial system through digital technologies became important to identify the determinants of Digital Financial Inclusion (DFI). In this context, the study aims to examine the use and accessibility of DFI and measure it specifically for Türkiye. The data is divided into two categories: demographic variables (gender, age, income, and education level) and variables related to DFI (account ownership, ownership of mobile money account, saving, and borrowing) and was compiled from the Global Findex Database 2021. Considering the binary structure of the dependent variable, the probit model was used in the study. Although our model findings indicate that demographic characteristics such as gender, education, and income have a significant effect on account ownership and savings, when marginal effects are taken into account, education is the strongest determinant of DFI. Regarding the income level, the coefficient estimates for the four income quintiles were found statistically significant. However, for lower-income quintiles, particularly the poorest 20 percent and the second 20 percent, the probability of being financially included was found to be significantly lower. When all variables are taken into consideration, women are more financially excluded than men, and there is significant gender inequality, especially in terms of account ownership.